1997
DOI: 10.1038/sj.ejcn.1600351
|View full text |Cite
|
Sign up to set email alerts
|

The prediction of total body water and extracellular water from bioelectric impedance in obese children

Abstract: Objectives: To assess the reliability of bioelectric impedance analysis (BIA) for predicting total body water (TBW) and extracellular water (ECW) in obese children. Design: Comparison of ®ve prediction models based on: (i) body weight (Wt), (ii) the impedance (Z) index (ZI height 2 /Z), (iii) the association of Wt and ZI, (iv) the body surface area (SA) to impedance ratio (SA:Z) and, (v) the body volume (V) to impedance ratio (V:Z). Subjects: Thirty obese and 25 control children of 11.2 AE 1.8 y of age. Measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…Aiming to assess the reliability of the BIA method with respect to the prediction of TBW in obese adolescents, Bedogni et al [32] have also found values close to the ones reported in the present investigation for TBW, in percentage (50.0%).…”
Section: Discussionsupporting
confidence: 84%
“…Aiming to assess the reliability of the BIA method with respect to the prediction of TBW in obese adolescents, Bedogni et al [32] have also found values close to the ones reported in the present investigation for TBW, in percentage (50.0%).…”
Section: Discussionsupporting
confidence: 84%
“…The R-based predictor commonly employed by BIA algorithms is the 'resistance index' (RI), ie the ratio of squared height (Ht) to R (Bedogni et al, 1996(Bedogni et al, , 1997. RI was originally devised because R is directly related to the length (L) and inversely related to the cross-sectional area (S) of an ohmic conductor.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of TBW volume data from a current sample of children is a useful comparison for clinical interpretations. The effect of fatness on TBW volume [13,14] is considered also due to the increased prevalence of obesity among U.S. children [4].…”
mentioning
confidence: 99%